Linking the knowledge-capital model of foreign direct investment with national knowledge systems - Henk L.M. Kox (KVL Economic Policy Research, 2022)
The paper models the links between public and firm-level knowledge processes. The knowledge-capital (KC) theory assumes that firms use their private knowledge assets to set up foreign subsidiaries. Countries with large outward FDI stocks should have a relative abundance of proprietary knowledge assets. This has not yet been adequately tested. Our model allows to test it by concentrating on national public knowledge inputs that are encapsulated in proprietary knowledge assets of firms. Using a rich international dataset we confirm the basic tenet of the KC theory and show the important role of public knowledge production for outward FDI.
Keywords: O34; O31; D22; D83; F23; 330; Foreign Direct Investment; Knowledge Transfer and Innovation; Knowledge Assets; Public Knowledge Creation; Multinational Companies; Empirical test; world coverage 2000-2020)